2023
DOI: 10.3390/polym15132911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Aging on Fatigue and Thermal Cracking Performance of Polyphosphoric Acid and Styrene–Butadiene–Styrene-Modified Bio-Blend Bitumen

Abstract: Polyphosphoric acid (PPA) and styrene–butadiene–styrene (SBS) were adopted to produce PPA-SBS-modified bio-blend bitumen, which achieved excellent mechanical performance. However, its long-range performance, such as the fatigue and thermal cracking behavior under long-term thermal oxidation, is not well understood. Therefore, a pressure aging vessel (PAV) system was applied to simulate the aging behavior of the bitumen under the action of thermal oxidation. Then, a linear amplitude sweep (LAS) test combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The research showed that the high-temperature deformation resistance and low-temperature crack resistance of the SBR/PP composite-modified asphalt mixture were improved, and its fatigue life was 50% higher than that of SBS-modified asphalt. Wang et al [ 13 ] produced PPA-SBS-modified bio-blend bitumen by adopting polyphosphoric acid (PPA) and styrene-butadiene-styrene (SBS), which has been experimentally proven to possess excellent thermal cracking and fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The research showed that the high-temperature deformation resistance and low-temperature crack resistance of the SBR/PP composite-modified asphalt mixture were improved, and its fatigue life was 50% higher than that of SBS-modified asphalt. Wang et al [ 13 ] produced PPA-SBS-modified bio-blend bitumen by adopting polyphosphoric acid (PPA) and styrene-butadiene-styrene (SBS), which has been experimentally proven to possess excellent thermal cracking and fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%